The assessment of health and nutritional status of seniors staying in in-patient healthcare institutions - Kołpa, Małgorzata; Jurkiewicz, Beata; Motyka, Anna (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Introduction. Changes progressing over time in seniors’ bodies, as well as socio-economic and psychological factors contribute to the poor nutritional status of the elderly. Although both malnutrition and obesity may result in increased morbidity in this age group, they continue to constitute an underreported problem in Poland. Objective. The aim of the thesis was to evaluate the health and nutritional status of seniors (65+) currently residing in hospitals. Material and methods. The research was conducted from October to November 2015 among 150 patients of three Małopolska’s hospitals. The studied group comprised 76 women (50.67%) and 74 men (49.33%) aged 65–96 (SD = 7.45). The utilised research method involved diagnostic surveys and interviews. To assess the nutritional status, a shortened Multi Nutritional Assessment (MNA) questionnaire and the author’s original interview questionnaire were used. Results. The most common chronic diseases in the studied group were cardiovascular diseases (n = 147; 98%), bone and joint diseases (n = 87; 58%), and sensory organ diseases (n = 85; 56.67%). Some of the respondents (n = 28; 18.67%) were bed- or chair-ridden, while 25 people (16.66%) could get out of bed, but not leave their domiciles. Nutritional disorders were diagnosed in a total of 46.67% of the respondents. People declaring themselves to be physically inactive were worse nourished than other respondents (p < 0.001). Moreover, a larger number of comorbidities and the occurrence of urogenital, bone and joint, neurological, or sensory organ diseases were related to worse nutritional statuses of the respondents (p < 0.05). Additionally, the more oral drugs the patients took, the worse their nutritional status was (p < 0.001). Conclusions . Nutritional disorders were diagnosed in nearly half of the studied seniors. The worse nutritional status in the studied group was notably associated with physical inactivity, a larger number of comorbidities, and with oral medication intake, as well as with the occurrence of urogenital, bone and joint, neurological, and sensory organ diseases.